CHARACTERISTIC OF CHRONIC MYELOGENOUS LEUKEMIA PATIENTS AT THE POLYCLINIC OF ONCOLOGY, DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA IN 2017 - M. Rifqi Wiyono; Siprianus Ugroseno Yudho Bintoro; Yetti Hernaningsi (Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: Chronic myelogenous leukemia (CML) is a myeloproliferative neoplasm because of the reciprocal translocation of chromosome 22 to chromosome 9. In the United States, the incidence of CML is 1.9 cases per 100,000 people. Whereas in Indonesia, there is no specific national data on CML prevalence, especially regarding the clinical profile, even though the cancer cases reach 1.4 per 1,000 population. Objective: To evaluate the characteristics and clinical features of CML patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Materials and Methods: This was a cross-sectional descriptive study with data from the medical records of CML patients in 2017 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The sample in this study was CML patients with positive Breakpoint Clusters Region- Abelson (BCR-ABL), having a minimum age of 18 years and equipped with epidemiological data, complete blood count data, and peripheral blood smear data. Results: Thirty-three patients met the study criteria. The sample was predominantly male, with a ratio of 1.06 : 1 to female patients with a median age of 40 years. Spleno-megaly was found in 87.9% of the patients. The average results of leukocyte, platelet, and hemoglobin counts were 254.58 x 103/μL, 557 x 103/μL, and 9.55 g/dL. From the results of peripheral blood smear obtained normochromic normocytic anisopoikilo-cytosis erythrocyte (57.6%), all patients had a profile of increased leukocytes with blast presence in 97% of the patients, and 51.5% had a profile of an increase in platelets and the discovery of giant platelets in 33.3% of the patients. Conclusion: The sample was predominantly male with the highest incidence at a younger age range of 21-30 years. The clinical characteristics showed high leukocytosis with various stage of maturation and a tendency to develop grade 2 normocytic normochromic anemia and thrombo-cytosis was found in the patients.